2013
DOI: 10.1016/j.otsr.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Coracoid bone block versus arthroscopic Bankart repair: A comparative paired study with 5-year follow-up

Abstract: Level IV (retrospective study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 32 publications
2
87
1
3
Order By: Relevance
“…In our pilot study [3], the recurrent rate of shoulder instability was 24% after arthroscopic Bankart repair and 12% after the Latarjet procedure. To identify a relative difference, 80 patients would have to be included in each group (for a power of 80% and a risk of a Type I error of 5%).…”
Section: Power Analysismentioning
confidence: 63%
See 1 more Smart Citation
“…In our pilot study [3], the recurrent rate of shoulder instability was 24% after arthroscopic Bankart repair and 12% after the Latarjet procedure. To identify a relative difference, 80 patients would have to be included in each group (for a power of 80% and a risk of a Type I error of 5%).…”
Section: Power Analysismentioning
confidence: 63%
“…Nevertheless, the choice of a technique depends often on the surgeon's training or preferences. In a pilot study [3] comparing 51 patients undergoing arthroscopic Bankart repair to 51 patients undergoing the open Latarjet procedure, we found no differences between the approaches in terms of shoulder stability with the numbers available; however, we were concerned that insufficient followup duration and low statistical power might have contributed to the study's inability to detect a difference between these procedures.…”
Section: Introductionmentioning
confidence: 83%
“…Shah et al reported using canulated screws as a risk factor [16]. Three cases of recurrency in each group constituted 6.2% in OPEN and [24]. In OPEN group two of three cases were related with the graft osteolysis and one with traumatic graft fracture but these facts remained statistically insignificant.…”
Section: Complications Recurrence and Revisionsmentioning
confidence: 99%
“…The rate of recurrent instability is 1.7-14.2 %, with a mean of 6.8 % [ 97 -100 ]. In a recent study, the rate of recurrent instability following a Latarjet reconstruction was two times lower than that following an arthroscopic Bankart repair [ 101 ]. In long-term follow-up, Lädermann et al reported recurrent instability or subluxation in only 2 of 117 (1.7 %) patients.…”
Section: Advantages and Pitfalls Complicationsmentioning
confidence: 95%